Silychristin and isosilychristin from the fruits of Silybum marianum (L.) Gaertin - Diep, Trinh Thi; Kiem, Phan Van; Dong, Nguyen Thuong; Tung, Nguyen Huu; Bang, Bui Thi; Minh, Chau Van; Braca, Alessandra (Vietnam Journal of Chemistry, 2014)
By various chromatography methods, two flavonolignan silychristin (1) and isosilychristin (2)were isolated from the fruits of Silybum marianum (L.) Gaertn. cultivated in the North of Vietnam. Their structures were elucidated by analyses of the NMR (1D-, 2D-NMR) and ESI spectra. This is the first report of both 1 and 2 from S. marianum cultivated in Vietnam